2021
DOI: 10.1103/physrevlett.126.107203
|View full text |Cite
|
Sign up to set email alerts
|

Classical Spin Liquid or Extended Critical Range in h - YMnO3 ?

Abstract: Neutron spectroscopy on the classical triangular-lattice frustrated antiferromagnet h-YMnO 3 reveals diffuse, gapless magnetic excitations present both far below and above the ordering temperature. The correlation length of the excitations increases as the temperature approaches zero, bearing a strong resemblance to critical scattering. We model the dynamics in the ordered and correlated disordered phase as critical spin correlations in a two-dimensional magnetic state. We propose that our findings may provide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…This overall behavior is similar to recent observations in a similar compound, the classical spin liquid h-YMnO 3 , which is a triangular-lattice Heisenberg magnet with S = 2 [48]. These single-crystal neutron studies showed that small 2D clusters fluctuate in the classical spin liquid regime and coexist with the spin waves below the 3D ordering transition in a noninteracting manner.…”
Section: Classical Spin Liquid Phasesupporting
confidence: 89%
“…This overall behavior is similar to recent observations in a similar compound, the classical spin liquid h-YMnO 3 , which is a triangular-lattice Heisenberg magnet with S = 2 [48]. These single-crystal neutron studies showed that small 2D clusters fluctuate in the classical spin liquid regime and coexist with the spin waves below the 3D ordering transition in a noninteracting manner.…”
Section: Classical Spin Liquid Phasesupporting
confidence: 89%
“…The first commissioning phase allowed testing CAMEA under various setup, covering different scientific topics. Most results will be communicated in separate publications [10] [11]. Here, we focus on an experiment using a MnF 2 single crystal of 6.2 g. The the spin waves for this spin 5/2 compound have been extensively studied [12], which makes this crystal an ideal calibration sample [13].…”
Section: Spin Waves In Mnf2mentioning
confidence: 99%
“…The software has been written with focus on being userfriendly, offering a scripting, a command line, and a graphical interface. The software was successfully used during the commissioning phase of the CAMEA spectrometer [9] and subsequently for the data treatment of acquired data [10,11].…”
Section: Introductionmentioning
confidence: 99%